2016
DOI: 10.1089/end.2015.0642
|View full text |Cite
|
Sign up to set email alerts
|

Cost Analysis of Flexible Ureteroscope Repairs: Evaluation of 655 Procedures in a Community-Based Practice

Abstract: Expenses associated with instrument repair can significantly impact a procedure's net revenue, thus efforts should be made to minimize instrument breakage. The expense of repairing a flexible ureteroscope per procedure can be significant and needs to be considered when pricing this procedure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
37
0
3

Year Published

2017
2017
2019
2019

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(42 citation statements)
references
References 19 publications
2
37
0
3
Order By: Relevance
“…The need for scope replacement, maintenance, and repair is one area that has been studied with regard to flexible ureteroscope usage. 19,20 Regarding failure of LithoVue, we experienced five occurrences of scope failure intraoperatively. The overall LithoVue failure rate of 4.4% was comparable with that of our reusable ureteroscopes (7.7%) and consistent with recent failure rates reported in the literature for reusable ureteroscopes.…”
Section: Discussionmentioning
confidence: 99%
“…The need for scope replacement, maintenance, and repair is one area that has been studied with regard to flexible ureteroscope usage. 19,20 Regarding failure of LithoVue, we experienced five occurrences of scope failure intraoperatively. The overall LithoVue failure rate of 4.4% was comparable with that of our reusable ureteroscopes (7.7%) and consistent with recent failure rates reported in the literature for reusable ureteroscopes.…”
Section: Discussionmentioning
confidence: 99%
“…In a multi-center clinical trial, Knudsen et al found that flexible ureteroscope required fixing after its use in 5.3–18 patients (2830). In addition, according to statistics from multiple articles, the main reasons for repair were the decreased capacity of active bending, the decreased image quality caused by fiber cuts and the sparking of laser in lens barrel (2832). It is necessary to protect the flexible ureteroscope during operation.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that single‐use fURS are becoming more economically viable, especially in lower‐volume centers and for cases with a higher risk of damage to reusable fURS . Several studies have shown that reusable fURS suffer damage requiring repair after 10–25 cases . Once a ureteroscope has been repaired, it is more likely to be damaged again, requiring further repair .…”
Section: Introductionmentioning
confidence: 99%